Load Voltage Balancing by Equalization of Conduction Angle in Hybrid Modular Multilevel Converter - Mr. Balasaheb J. Pawar, Dr. Vitthal J. Gond (International Journal of Advanced Science and Technology, 2020)
Conventional multi-carrier pulse width modulation (PWM) techniques increases controlling complexity in modular multilevel converters (MMC). To provide the DC fault handling as well as to minimize the density of switching elements and hence the switching losses, hybrid MMC (HMMC) is proposed by few researchers. The HMMC is built up by individually controllable sub-modules (SMs). Therefore the converter can act as a controllable voltage source converter, with a desired number of discrete voltage steps. To avoid the use of complex multi-carrier PWM, this paper investigates an alternative solution, where a single triangular carrier signal and few active reference voltage sources and hence called as multiple active reference sources PWM technique (MARPWM), are used to insert/bypass the SMs of HMMC. A closed loop controlled MARPWM is presented to provide three phase load voltage at balanced/unbalanced load conditions with less harmonics and improved power factor of HMMC. Also the feature of MARPWM technique is to keep the control on SM capacitor voltage balancing. Various existing switching techniques are studied for the conclusion with this newly proposed method to make the system more robust in operation with less complexity in design and control.